Cytosolic DNA sensors in neurodegenerative diseases: from physiological defenders to pathological culprits - Jiatian Xie; Jinping Cheng; Ho Ko; Yamei Tang (EMBO Molecular Medicine, 2024)
Abstract Cytosolic DNA sensors are a group of pattern recognition receptors (PRRs) that vary in structures, molecular mechanisms, and origins but share a common function to detect intracellular microbial DNA and trigger the innate immune response like type 1 interferon production and autophagy. Cytosolic DNA sensors have been proven as indispensable defenders against the invasion of many pathogens; however, growing evidence shows that self-DNA misplacement to cytoplasm also frequently occurs in non-infectious circumstances. Accumulation of cytosolic DNA causes improper activation of cytosolic DNA sensors and triggers an abnormal autoimmune response, that significantly promotes pathological progression. Neurodegenerative diseases are a group of neurological disorders characterized by neuron loss and still lack effective treatments due to a limited understanding of pathogenesis. But current research has found a solid relationship between neurodegenerative diseases and cytosolic DNA sensing pathways. This review summarizes profiles of several major cytosolic DNA sensors and their common adaptor protein STING. It also discusses both the beneficial and detrimental roles of cytosolic DNA sensors in the genesis and progression of neurodegenerative diseases.